2019
DOI: 10.1080/13825585.2019.1700898
|View full text |Cite
|
Sign up to set email alerts
|

Shared neural recruitment across working memory and motor control tasks as a function of task difficulty and age

Abstract: Past research has suggested that working memory and motor control may engage similar cognitive and neural mechanisms in older adults. However, much of this evidence arises from comparisons across behavioral and imaging studies that test only one of the foregoing functional domains. The current study expanded this work by examining both tasks within the same group of older adults. In addition, we examined whether the recruitment of common mechanisms increased with both task difficulty and with increasing age. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…CRUNCH has not been investigated thoroughly in walking tasks where task difficulty is parametrically increased, such as walking on uneven terrains. Initial investigations in a visuomotor grasp task by Gerver et al (2019) showed that, in older adults, performance of the grasp task declined as task difficulty was increased. Along with the decrease in motor performance, they observed increases in brain activity across frontoparietal regions.…”
Section: Discussionmentioning
confidence: 99%
“…CRUNCH has not been investigated thoroughly in walking tasks where task difficulty is parametrically increased, such as walking on uneven terrains. Initial investigations in a visuomotor grasp task by Gerver et al (2019) showed that, in older adults, performance of the grasp task declined as task difficulty was increased. Along with the decrease in motor performance, they observed increases in brain activity across frontoparietal regions.…”
Section: Discussionmentioning
confidence: 99%
“…Although we included a measure of general processing speed, we focused on the three core cognitive control functions, working memory/updating, inhibitory control, and cognitive flexibility ( Miyake and Friedman, 2012 ). While many multisensory integration processes occur automatically in association cortices, cognitive control processes involve frontal lobe circuitry ( D’Esposito and Postle, 2015 ; Gerver et al, 2020 ), which is most sensitive to aging. The following paragraphs summarize age-related differences in our cognitive measures and discuss how sensorimotor processes draw on processing speed, working memory, inhibitory control, and cognitive flexibility.…”
Section: Introductionmentioning
confidence: 99%
“…Working memory is the temporary storage and manipulation of information, and is an intersection between memory, perception, and the attentional control of behavior [11], and is necessary for motor skill acquisition [12,13]. Indeed, the motor system and working memory tasks recruit common neural pathways [14][15][16][17][18]. Considering that sleep restriction negatively affects working memory, it follows that sleep restriction may also affect performance of motor tasks that rely on working memory.…”
Section: Introductionmentioning
confidence: 99%